What's Class Got To Do With It? American Society in the Twenty-First Century - Camfield, David (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "What's Class Got to Do with It? American Society in the Twenty-First Century," edited by Michael Zweig.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Essays; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes